Fraud Hexagon Theory dalam Memprediksi Financial Statement Manipulation: Bukti dari Perusahaan Properti dan Real Estate yang Terdaftar di ISSI - Mustafa, Zulhikmah Putri; Hadinata, Sofyan (IAIN Kudus, 2024)
This study investigates the effect of fraud hexagon theory on financial statement manipulation. The six variables of the fraud hexagon theory consist of stimulus, capability, collusion, opportunity, rationalization, and ego. Property and real estate companies included in the calculation of the Indonesian Sharia Stock Index (ISSI) for the 2016-2022 period are the objects of this study. The data sources were taken from the company's annual report and financial statement. The sampling technique uses purposive sampling or by determining certain criteria. From this sampling, 126 company-year observations were obtained. A logistic regression analysis technique was used to analyze the data. The results of the data testing showed that rationalization had a positive effect on the manipulation of financial statements. Meanwhile, the other five variables, namely stimulus, capability, collusion, opportunity, and ego, failed to predict financial statement manipulation.